STUDY OF MAGNITUDE OF UTI CAUSED BY ESBL-PRODUCING ESCHERICHIA COLI AND ASSOCIATED RISK FACTORS - CHATURVEDI, ADYA; GUPTA, BHAVNA; CHATURVEDI, ASHUTOSH; SISODIYA, RASHMI; SHARMA, RAJNI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Globally, urinary tract infections (UTIs) caused by Escherichia coli that produce extended-spectrum lactamase (ESBL) have become more common. Our study determined the magnitude of UTI occurring due to ESBL-producing E. coli and associated risk factors. Different methods for their phenotypic detection were also compared. Methods: Uropathogenic E. coli isolated in significant numbers were assayed microbiologically. E. coli isolates (n=247) that were found significant in number tested for ESBL production using three different phenotypic methods: Phenotypic combined disk diffusion test (PCDDT), double-disk approximation test (DDAT), and E-test for ESBL production. An antibiotic susceptibility test was performed for different antibiotics. Various risk factors associated with UTIs were correlated with ESBL- and non-ESBL-producing E. coli. Results: We found that diabetes mellitus type 2 was the most common risk factor for UTI caused due to ESBL-producing E. coli (25%). Pregnant females and patients having recurrent UTI showed less positivity for ESBL production. DDAT detected 32 ESBL-positive isolates and PCDDT detected 37 positive isolates. E-test was taken as the gold standard for ESBL detection which detected 49 isolates as ESBL producers. The highest sensitivity (71.2%) and specificity (75%) were shown by PCDDT. Conclusion: According to the study conducted, it was concluded that PCDDT was the most reliable and economic method for phenotypic detection of ESBL.